1999
DOI: 10.1142/s0217979299002629
|View full text |Cite
|
Sign up to set email alerts
|

QUANTUM-CHEMISTRY STUDY OF SEMICONDUCTOR SYSTEMS: THE INITIAL OXIDATION OF THE (111)Si-H SURFACE

Abstract: We propose a well-defined procedure to adapt a Quantum-Chemistry technique for the study of semiconductor structures. The procedure comprises use of a Bloch-periodic version of the standard molecular code and a nanocrystal cluster model. We reparametrize according to this procedure the MNDO/AM1 technique for Si and O and present this new parametrization AM1/Crystal. We apply AM1/Crystal to study oxidation of the hydrogenated silicon(111) surface, at the initial stages, when the absorbed oxygen atoms form isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
2
5
0
1
Order By: Relevance
“…In particular for the AM1/Crystal parametrization, a detailed description can be found in Ref. [23]. We obtain best fits, within 4% of the experimental value, (a) to the geometries and vibrational properties of the molecules, with the standard molecular code and the new parametrization, and (b) for the lattice parameters of the crystals, with the periodic supercell NDO code.…”
Section: Nanocrystals and Quantum-confinement Effectsmentioning
confidence: 53%
See 3 more Smart Citations
“…In particular for the AM1/Crystal parametrization, a detailed description can be found in Ref. [23]. We obtain best fits, within 4% of the experimental value, (a) to the geometries and vibrational properties of the molecules, with the standard molecular code and the new parametrization, and (b) for the lattice parameters of the crystals, with the periodic supercell NDO code.…”
Section: Nanocrystals and Quantum-confinement Effectsmentioning
confidence: 53%
“…, and the CI value effect of relaxation is an expansion of the Si core of the particles, relative to nanocrystals (such non-linear relaxations are also found [23] to a lesser extent in hydrogenated Si(111) surfaces). This results are relevant to the debate on the dimensionality of the luminescent structures in po-Si, since it is shown that particles of this size may cause the phonon lines seen [34] experimentally.…”
Section: Si : H Nanoparticles and Surface Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Outras aproximações para a simulação de sistemas periódicos a partir de aglomerados finitos utilizam o conceito de pseudo-átomos [93,94] que agem como saturadores na "superfí-cie" do cluster, para impedir a presença de orbitais "flutuantes" (dangling bonds) ou ligações quebradas que perturbam toda a estrutura eletrônica do sistema. No formalismo do cluster cíclico, nas extremidades do sistema são incluídas duplicatas dos átomos correspondentes da extremidade oposta, de forma que mesmo os átomos que formariam a superfície do sistema estão "cercados de átomos", criando assim um sistema cíclico.…”
Section: A Parametrização Msindounclassified